Pharmacist role to enhance the prescribing of hospital discharge medications for patients after heart attack - Amina M. Jabri; Hayder Ch. Assad; Ali Azeez Al-Jumaili (Elsevier, 2020)
Objectives: This study aimed to explore the cardiologist adherence with ACC/AHA guidelines on discharge medications for patients admitted with acute coronary syndrome (ACS), assess the predictors of cardiologist non-adherence and measure the impact of pharmacist intervention on improving guideline adherence. Methods: The study included two consecutive phases: observation and intervention. It was carried out at Al-Najaf Center for Cardiac Surgery and Catheterization, Iraq, from August through December 2018. In the observation phase, medical records were reviewed retrospectively in order to assess the adherence to guideline. The intervention phase was performed prospectively by the clinical pharmacist, who conducted interventions including auditing, feedback and discussion with every prescriber. The reference of the recommendations was the guideline of American Heart Association/American College of Cardiology guideline (AHA/ACC). The primary outcome was the proportion of patients discharged with optimal treatment. Independent T-test was used to measure the difference in the means of age between the two patient groups. For categorical variables (gender, diagnosis, and comorbidities), chi-square test was used. Binary logistic regression was used to identify patient and disease characteristics associated with receiving optimal discharge regimen. Results: The observation phase included 100 patients with ACS, while the intervention phase included 105 patients. A total of 50 interventions were performed by pharmacist, of which adding necessary medication was the most frequent (88%), followed by dose optimization (10%), and removing medication duplication (2%). Seventy-four percent of the provided recommendations were accepted by the cardiologists. Pharmacist intervention caused significant (P-value < 0.05) improvement (increasing) in the prescribing of β-blockers, ACE inhibitors/ARBs, statins, and the proportion of patients who received all optimal five therapies (from 35% in observation phase to 80% after intervention). Conclusion: This study showed that pharmacist intervention had a considerable positive impact on the cardiologist prescribing pattern of the essential discharge medications for patients with ACS which could improve patient clinical outcomes. Keywords: Acute coronary syndrome, Heart attack, Pharmacist intervention, Secondary prevention, Cardiology guideline